2011
DOI: 10.1158/2159-8290.cd-11-0087
|View full text |Cite
|
Sign up to set email alerts
|

The Drug-Induced Degradation of Oncoproteins: An Unexpected Achilles' Heel of Cancer Cells?

Abstract: Many targeted therapies against cancer are aimed at inhibiting the enzymatic activity of kinases. Thus far, this approach has undoubtedly yielded significant clinical improvements, but has only rarely achieved cures. Other drugs, which selectively elicit proteasome-dependent degradation of oncoproteins, induce the loss of cancer cell self-renewal and promote cell differentiation and/or apoptosis. In acute promyelocytic leukemia, the cooperative degradation of PML/RARA by arsenic and retinoic acid cures most pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 81 publications
(79 reference statements)
2
42
0
Order By: Relevance
“…13,15,39 These observations further strengthen the proposed link between LIC activity and PML-RARA loss. 10,14,39 VPA may synergize with ATRA for LIC clearance in vivo We then analyzed the effect of the combination of VPA and ATRA in vivo.…”
Section: Vpa Induces Tumor Regression and Apls Differentiation In Vivosupporting
confidence: 71%
See 1 more Smart Citation
“…13,15,39 These observations further strengthen the proposed link between LIC activity and PML-RARA loss. 10,14,39 VPA may synergize with ATRA for LIC clearance in vivo We then analyzed the effect of the combination of VPA and ATRA in vivo.…”
Section: Vpa Induces Tumor Regression and Apls Differentiation In Vivosupporting
confidence: 71%
“…13,15,39 These observations further strengthen the proposed link between LIC activity and PML-RARA loss. 10,14,39 VPA may synergize with ATRA for LIC clearance in vivo We then analyzed the effect of the combination of VPA and ATRA in vivo. Interestingly, when primary leukemias were pre-treated with VPA for 1 day, PML-RARA protein levels were reduced in ATRA plus VPA-treated mice compared with ATRA-treated ones (Figure 5a), though differentiation was essentially unaltered at 2 days of exposure to drugs (Figure 5b).…”
Section: Vpa Induces Tumor Regression and Apls Differentiation In Vivosupporting
confidence: 71%
“…37 Importantly, the antileukemic and differentiation effect of ATRA in APL has been recently linked to its ability to induce autophagy-dependent degradation of the PML-RARA/RARa oncoprotein. [38][39][40] The discovery that P2RY6 ligands such as UDP or P2RY6 agonists are able to restore normal differentiation in some CMML patients through the PRKAA1 reactivation is exciting. In agreement with these findings, it has been recently reported that 5-aminoimidazole-4-carboxamide ribonucleoside, an PRKAA activator, enhances ATRA-mediated differentiation of promyelocytic NB4 cells and, as a single agent induces the expression of cell surface markers associated with mature monocytes and macrophages in the acute myeloid leukemia cell line www.tandfonline.comU937.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important therapeutic relevance, as IFNa promotes PML-and SUMO-dependent degradation of toxic proteins in the brain 62,63 or of the HTLV-I leukemia oncoprotein Tax 64 , with unambiguous clinical benefit 62,65,66 . Thus, similar to therapies based on manipulation of ubiquitin-dependent degradation 67,68 , this could pave the way to IFN-triggered, SUMO-based therapies promoting the proteolytic clearance of undesirable proteins 68 .…”
Section: Articlementioning
confidence: 99%